Biosafety and perceived commercial risks: The role of GM-free private standards - Gruère, Guillaume P.; Sengupta, Debdatta (International Food Policy Research Institute, 2009)
This brief summarizes a study on commercial risks and the role of GM-free private standards in biosafety decisionmaking in developing countries. The findings are used to suggest a straightforward decisionmaking framework to help separate real commercial risks from other perceived risks.